Loss of osteoglycin promotes angiogenesis in limb ischaemia mouse models via modulation of vascular endothelial growth factor and vascular endothelial growth factor receptor 2 signalling pathway. Issue 1 (23rd October 2016) - Wu, Qi-Hong; Ma, Yu; Ruan, Cheng-Chao; Yang, Yan; Liu, Xin-He; Ge, Qian; Kong, Ling-Ran; Zhang, Ji-Wei; Yan, Chen; Gao, Ping-Jin
Abstract : Objective: Osteoglycin (OGN) has been noted for its implication in cardiovascular disease in recent studies. However, the relationship between OGN and angiogenesis remains unknown. Therefore, we aimed to investigate the effect of OGN on ischaemia-induced angiogenesis and to address the underlying mechanisms. Methods and results: The expression of OGN was decreased in a limb ischaemia mouse model. OGN knockout (KO) mice were used to further understand the role of OGN after ischaemia. The perfusion recovery rate after femoral artery ligation was higher in OGN KO mice than in wild-type (WT) mice. The capillary density in the gastrocnemius muscle of the ischaemic limb was also higher in OGN KO mice. Moreover, ex vivo aortic ring explants from OGN KO mice exhibited stronger angiogenic sprouting than those from WT mice. In human umbilical vein endothelial cells (HUVECs), OGN knockdown enhanced endothelial cell (EC) activation, including tube formation, proliferation, and migration. In contrast, OGN overexpression inhibited HUVEC activation. Mechanistic studies revealed that OGN associates with vascular endothelial growth factor receptor 2 (VEGFR2) and negatively regulates the interaction of vascular endothelial growth factor (VEGF) and VEGFR2, thereby negatively modulating the activation of VEGFR2 and its downstream signalling pathways. Consistently, the pro-angiogenic effect of OGN KO was abrogated by VEGFR2 inhibition, supporting the critical role of VEGFR2 signalling in OGN-mediated regulation of angiogenic function. Conclusions: OGN plays a critical role in negatively regulating ischaemia-induced angiogenesis by inhibiting VEGF–VEGFR2 signalling and thereby attenuating EC tube formation, proliferation, and migration. Thus, OGN may be a novel therapeutic target for ischaemic vascular diseases.